Modelling of adsorption-based refrigeration system - Liu, Yue (2008)
This thesis presents several numerical models including thermodynamic model, lumped model and heat and mass transfer model for different zeolite/water adsorption refrigeration cycles to investigate the effects of parametric and operating conditions on system performance. Experiments were also carried out to validate the heat and mass transfer model.